Long-term prognosis of tooth autotransplantation: a systematic review and meta-analysis. Issue 5 (May 2016) - Machado, L.A.; do Nascimento, R.R.; Ferreira, D.M.T.P.; Mattos, C.T.; Vilella, O.V.
Abstract: The aim of this study was to systematically review the prognosis of autotransplanted teeth followed up for a period of 6 years or more. A literature search was conducted in five databases and the eligibility criteria were established. The outcomes evaluated were the survival rate, percentage of abnormal mobility, pulpal conditions, and percentage of root resorption. The searches identified 1848 articles, and after evaluation against the eligibility criteria, six were included. Data related to outcome measures were extracted from the studies and a meta-analysis was performed. Survival rates ranged from 75.3% to 91% and the meta-analysis showed an effect size of 81% ( P  < 0.0001). The percentage ankylosis ranged from 4.2% to 18.2% and the effect size was 4.8% ( P  < 0.0001). Root resorption percentages ranged from 3% to 10% and the effect size was equal to 4% ( P  < 0.0001). It was not possible to perform a meta-analysis of data on pulpal conditions and percentage of teeth with abnormal mobility. The results of this study showed the survival rate to be excellent, considering the observation period. The rates of ankylosis and root resorption, despite their low values, influence the prognosis of transplanted teeth.